2019
DOI: 10.4236/ce.2019.1012225
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Awareness towards the Use of MOOCs in Teaching and Learning

Abstract: In today's era of globalisation, Massive Open Online Courses (MOOCs) are no longer a stranger among universities and higher institutions. Many universities and colleges have started to make use of MOOCs as the platform for online learning in combination with face to face classroom for university courses. However, there are still many learners, especially university students who are not aware and familiar with the existence of Massive Open Online Courses (MOOCs). In conjunction to this, researchers intended to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…However, MOOCs are versatile ways that educational institutions have to offer in order to facilitate access to educational across world [23]. These results are consistent with other MOOCS studies; for instance [24], MOOCs are slowly emerging and evolving in higher education institutions.…”
Section: Educational Institutions Adoptsupporting
confidence: 88%
“…However, MOOCs are versatile ways that educational institutions have to offer in order to facilitate access to educational across world [23]. These results are consistent with other MOOCS studies; for instance [24], MOOCs are slowly emerging and evolving in higher education institutions.…”
Section: Educational Institutions Adoptsupporting
confidence: 88%
“…Such notion is supported by a study conducted by Makhtar et al [20] that concur the importance of innovative and creative teaching methods to be deployed by teachers in class, as it can increase the interest and attitude of students to continue to be consistent and ultimately show good performance in class. This is in line with Rusli et al [21] who also reported that effective teacher teaching strategies such as student-centered teaching methods in the form of small group learning has a significant correlation with the students' achievement due to its capability to shape the students' thinking process.…”
Section: Introductionsupporting
confidence: 88%
“…According to Mattar (2018), we should outsource certain cognitive work to machines as they are more effective in completing certain jobs than humans. In online courses, the learners often have the option of interacting with the course materials at any time and place (Rusli et al, 2019).…”
Section: B Connectivism Theorymentioning
confidence: 99%